fMRI Brain Activation in a Finnish Family With Specific Language Impairment Compared With a Normal Control Group. - Hugdahl, Kenneth; Gundersen, Hilde; Brekke, Cecile (Journal of Speech, Language & Hearing Research, 2004)
The aim of the present study was to investigate differences in brain activation in a family with SLI as compared to intact individuals with normally developed language during processing of language stimuli. Functional magnetic resonance imaging (fMRI) was used to monitor changes in neuronal activation in temporal and frontal lobe areas in 5 Finnish family members with specific language impairment (SLI) and 6 individuals in an intact control group. Magnetic resonance (MR) image acquisitions were made while the participants listened to series of isolated vowel sounds, pseudowords, and real words. The stimuli were digitized single Finnish vowel sounds, 3-phoneme pseudowords, and 3- and 4-phoneme real words. MR scanning was made with a 1.5 T Siemens Vision Plus scanner, and the auditory stimuli were presented according to an event-related fMRI design. The results showed significant differences between the family with SLI and the intact control group with regard to brain activation in areas in the temporal and frontal lobes. Temporal lobe activation differences were most pronounced in the middle temporal gyrus bordering the superior temporal sulcus. The control participants also activated an area in the inferior frontal lobe in BA 44. It is concluded that individuals with SLI showed reduced activation in brain areas that are critical for speech processing and phonological awareness. The present functional brain imaging data fit well with other recent imaging data that also showed structural abnormalities in the same and neighboring areas. Reprinted by permission of the publisher.